Inferior shoulder dislocation with greater tuberosity avulsion fracture treated with Traction-Countertraction method in a rural hospital: A case report and literature review - Kevin Kusuman; Kadek Adit Wiryadana; Su Djie To Rante (DiscoverSys Inc., 2022)
Introduction. Inferior shoulder dislocation is considered a rare event. Although there is a seemingly low chance of occurrence, this condition should not be prematurely ruled out in the presence of acute shoulder pain. Case. A 45 years old woman complained of pain in her left shoulder and was unable to bring her arm lower than 90° after a car accident. The patient unintentionally put her left arm outstretched above her head to avoid head impact during the crash, causing hyperabduction of the shoulder. She experienced pain, numbness and could not move the ipsilateral hand. Her left arm was locked in hyperabduction (100°), and her elbow was extended. Close inspection showed a loss of left shoulder contour. On palpation, the humeral head was palpable in the axilla. Anteroposterior X-ray view confirmed inferior dislocation of the left shoulder with associated greater tuberosity fracture. A closed reduction under general anesthesia with the traction-counter traction technique was conducted as commonly used in rural settings. After perfect anatomical reduction was obtained and confirmed with X-ray, the patient was immobilized using an arm sling. The shoulder was immobilized for three weeks in adducted position to support soft tissue healing. Physiotherapy was started after three weeks. Conclusion. Inferior shoulder dislocation is a rare orthopedic pathology that should not be easily dismissed in post-traumatic shoulder pain. The mechanism of injury is characterized by downward force or lever mechanism on the hyperabducted arm. Orthopedic surgeons in rural areas could utilize the Traction-countertraction method.